Preoperative or Pre-procedural Fasting Guidelines in Patients Undergoing Elective Surgery and Procedures by the Royal College of Anesthesiologists of Thailand - Tangwiwat, Suwimon; Wongyingsinn, Mingkwan; Kasemsiri, Cattleya; Charoenraj, Pornarun; Bunchungmongkol, Nutchanart; Soonthornkes, Neranchala; Nongnuang, Krisana; Lekprasert, Varinee; Pattaravit, Ngamjit; Horatanaruang, Duenpen; Tirasuntornwong, Viranut; Pinsopon, Mitthira; et al. (Thai Journal of Anesthesiology, 2021)
This practice guidelines have been systematically complied from scientific evidence. Based on recommendations from the 2017 American Society of Anesthesiologists and the previous studies for preoperative fasting and the use of pharmacologic agents, this guidelines applied to the healthy patients undergoing elective surgery and procedures. The authors developed this guidelines to assist the practitioner and patient in making decisions on preoperative fasting to reduce the risk of pulmonary aspiration. This practice guidelines can be implemented as a local institutional policy as appropriate.